Mutualism ants and their insect partners - Stadler, Bernhard (Cambridge University Press, 2008)
A mutualism is an interaction between individuals of two different species of organism in which both benefit from the association. With a focus on mutualisms between ants and aphids, coccids, membracids and lycaenids, this volume provides a detailed account of the many different facets of mutualisms. Mutualistic interactions not only affect the two partners, but can also have consequences for higher levels of organization. By linking theory to case studies, the authors present an integrated account of processes and patterns of mutualistic interactions at different levels of organisation, from individuals to communities to ecosystems. Interactions between ants and their insect partners and their outcomes are explained from a resource-based, cost-benefit perspective. Covering a fascinating and growing subject in modern ecology, this book will be of interest to community and evolutionary ecologists and entomologists, at both research and graduate student level.